Development of Fluorescent Chemosensors for Calcium and Lead Detection - Liliana J. Gomes; Mani Outis; Clara S. B. Gomes; Augusto C. Tomé; Artur J. Moro (Molecules, 2024)
In the present work, several coumarin-3-carboxamides with different azacrown ether moieties were designed and tested as potential luminescent sensors for metal ions. The derivative containing a 1-aza-15-crown-5 as a metal chelating group was found to yield the strongest response for Ca2+ and Pb2+, exhibiting an eight- and nine-fold emission increase, respectively, while other cations induced no changes in the optical properties of the chemosensor molecule. Job’s plots revealed a 1:1 binding stoichiometry, with association constants of 4.8 × 104 and 8.7 × 104 M–1, and limits of detection of 1.21 and 8.04 µM, for Ca2+ and Pb2+, respectively. Computational studies suggest the existence of a PET quenching mechanism, which is inhibited after complexation with each of these two metals. Proton NMR experiments and X-ray crystallography suggest a contribution from the carbonyl groups in the coumarin-3-carboxamide fluorophore in the coordination sphere of the metal ion.